(untitled) (The International Journal for Scientific Research, 2026)
This research aims to promote the concept of conscious citizenship within the framework of the “Hopes and Aspirations” digital citizenship initiative at the Second Secondary School in Qara, Al-Jawf Education Department. This is achieved by utilizing digital technology tools and developing students’ behavioral and ethical awareness in the digital environment. The research stems from the importance of preparing a digital generation equipped with critical thinking skills, digital responsibility, and the ability to interact safely and consciously with modern technologies, in line with the objectives of the Kingdom’s Vision 2030. The initiative adopted a descriptive and applied methodology, based on analyzing the school’s current situation and developing awareness programs and practical applications within classrooms. It integrated active learning strategies and varied assessment methods (diagnostic, formative, and summative), in addition to activating community partnerships with families. Artificial intelligence tools and digital platforms were also employed to promote positive practices and measure their impact on digital behavior and learning outcomes. The results showed a significant improvement in students’ digital awareness, a decrease in some negative practices associated with the unsafe use of technology, and a growing sense of responsibility and self-discipline. The research recommends expanding the initiative to include sustainable training programs, strengthening integration between schools and families, and continuing to develop interactive digital content that supports national values and positive digital behavior.